Centennial-scale vegetation and North Atlantic Oscillation changes during the Late Holocene in the southern Iberia. (1st July 2016) - Ramos-Román, M.J.; Jiménez-Moreno, G.; Anderson, R.S.; García-Alix, A.; Toney, J.L.; Jiménez-Espejo, F.J.; Carrión, J.S.
Abstract: High-reso CE to lution pollen analysis, charcoal, non-pollen palynomorphs and magnetic susceptibility have been analyzed in the sediment record of a peat bog in Sierra Nevada in southern Iberia. The study of these proxies provided the reconstruction of vegetation, climate, fire and human activity of the last ∼4500 cal yr BP. A progressive trend towards aridification during the late Holocene is observed in this record. This trend is interrupted by millennial- and centennial-scale variability of relatively more humid and arid periods. Arid conditions are recorded between ∼4000 and 3100 cal yr BP, being characterized by a decline in arboreal pollen and with a spike in magnetic susceptibility. This is followed by a relatively humid period from ∼3100 to 1600 cal yr BP, coinciding partially with the Iberian-Roman Humid Period, and is indicated by the increase of Pinus and the decrease in xerophytic taxa. The last 1500 cal yr BP are characterized by several centennial-scale climatic oscillations. Generally arid conditions from ∼450 to 1300 CE, depicted by a decrease in Pinus and an increase in Artemisia, comprise the Dark Ages and the Medieval Climate Anomaly. Since ∼ 1300 to 1850 CE pronounced oscillations occur between relatively humid and arid conditions. Four periods depicted by relatively higher Pinus coinciding with the beginning and end of the Little Ice Age are interrupted by three arid events characterized by an increase in Artemisia. These alternating arid and humid shifts could be explained by centennial-scale changes in the North Atlantic Oscillation and solar activity. Highlights: We studied a late Holocene vegetation and fire record from southern Spain. A long-term aridification trend is observed, interrupted by shorter-scale variability. This study shows humidity changes during the last 4500 yr, related to NAO changes and solar variability.